Plant-insect interactions on dicots and ferns from the miocene of Argentina - Robledo, Juan Manuel (2018)
The study of plant-insect interactions provides valuable information about the ecology of feeding behavior and the relationships between the host plant and the producer insect. Records of feeding traces are relatively rare for the Miocene of South America. Here, new records of plant-insect interactions on dicot leaves and fern fronds from the middle and late Miocene of Argentina are presented. In total, 1204 dicot and fern impressions were analyzed including 384 from the San JoŚe Formation and 856 from the Palo Pintado Formation. Traces of arthropod herbivory are found on 303 foliar impressions, 288 from the Palo Pintado Formation and just 15 from the San JoŚe Formation. Forty-four percent of all traces were found on Thelypteris interrupta (Willd.) Iwatsuki 1963 (Thelypteridaceae), followed by Cedrela fissiliformis Anzótegui and Horn 2011 (Meliaceae) (15.1%) and Schinus herbstii Anzótegui 1998 (Anacardiaceae) (11.3%). Thelypteris interrupta is associated with a low diversity of Damage Types, mainly hole and window feedings, indicating a monospecific relationship with the trace maker. On the other hand, the high abundance and diversity of damage types found on C. fissiliformis and S. herbstii denote that these plants were hosting a more diverse group of arthropods. Likewise, the lower number of traces identified in the San JoŚe Formation corresponds to the xeric conditions established during the middle Miocene in northwestern Argentina. These conditions changed in the late Miocene, at least in some regions, to a humid climate, promoting an increase in phytophagy that is evidenced by the abundance recorded in the Palo Pintado Formation.